Two decades of research on migrant health in China: A systematic review. Lessons for future inquiry - Li Ling; Manju Rani; Yuanyuan Sang; Guiye Lv; Sarah L. Barber (United Nations Research Institute for Social Development (UNRISD), 2014)
This paper examines the adequacy, quality and relevance of existing evidence on migrant health in China as a guide to future research and policy. It uses a systematic review to identify publications on migrant health issues in China between 1985 and 2010 from selected databases. It also assesses the technical focus and methodologies for the 1,216 research articles retrieved. The volume of research on migrant health issues has grown nearly 55-fold between 1985-2000 and 2006-2010, with the publication of nearly 194 studies annually during the latter period. Almost two-thirds of the studies (68 per cent) sampled only migrants, with no comparison group either from destination urban areas or sending rural areas. Less than one-tenth of the studies evaluated a specific intervention (9 per cent); among those, most sampled only migrants and used a before-after design. The research tended to focus on communicable diseases (43 per cent), with HIV/AIDS accounting for 26 per cent. Research on health systems and non-communicable diseases represented 9 per cent and 13 per cent of the studies, respectively. More than half of the studies (54 per cent) were carried out in cities in four provinces, with few investigating family members left behind in rural areas. Despite a substantial increase in volume, research on migrant health in China has provided limited information to inform current policies and programmes. Most studies are descriptive and disproportionately focused on a handful of communicable diseases, neglecting some of the pressing policy-relevant issues in China on service access. Few studies have comparison populations. Increasing the rigour and relevance of future research will require better sampling frames with comparison populations; a focus on neglected research areas, including access to services; and partnerships with government and other agencies to evaluate specific interventions.
Keywords: 330